EVALUASI KUALITAS PENYELENGGARAAN BIMTEK PENINGKATAN KAPASITAS ANGGOTA DPRD KAB/KOTA/PROVINSI - Iffah Budiningsih; Efridani Lubis (Akademika, 2019)
The aim of the research is to evaluative and obtain empirical data about the quality of organizing " capacity building technical guidance of Member of Legislative districts/cities/provinces" organized by UIA-LPPM. The method of study using surveys with the target population is all participants technical guidance 2018/2019 during the period (6 months) that there were 6 times technical guidance activities. Sampling is done in a simple random sample, the amount of 50% of the total activities of the technical guidance, namely: three (3) events from event 6 times technical guidance as many as 86 people. Data analysis using SPSS program with a descriptive analysis. The research results showed that the participants opinion technical guidance provide that the quality of capacity building organization of Member of Legislative districts/cities/provinces " is a great fit with the needs = 25%; appropriate with needs = 69%; fit =; less appropriate = 0% and highly inappropriate = 0 %. The average opinion of the respondents give score = 4.1222 which means the quality of organizing "capacity building technical guidance of Member of Legislative districts/cities/provinces" in accordance with the needs of the participants technical guidance"; this needs to be maintained the quality of its commissioning and when necessary be present again.